EVALUATING THE ROLE OF PEDAL CIRCULATION IN WOUND HEALING OUTCOMES FOLLOWING BYPASS SURGERY IN CHRONIC LIMB-THREATENING ISCHEMIA (The Research of Medical Science Review, 2025)
Background: CLTI stands as a major PAD manifestation that develops when patients experience rest pain while experiencing non-healing wounds and developing gangrene in their peripheral areas. Bypass surgery is an essential treatment that restores blood flow to the limbs while speeding up the recovery of wounds. The specific relationship between pedal circulation and post-bypass surgical healing still needs more research because investigators have not properly examined this connection. Objectives: to analyze foot blood circulation affects healing studies for patients who need bypass surgery for CLTI. The research connects the patency of pedal arteries to wound closure rates and limb salvaging while investigating total clinical results. Study design: This retrospective cohort study Place and duration of study. Department Of Vascular Surgery CMH Rawalpandi from jan 2020 to jan 2024. Methods: 200 patients with CLTI who received bypass surgery from jan 2020 to jan 2024. The study used Doppler ultrasound and angiography to evaluate pedal circulation at different points during the study. Medical examination results divided the patients into two groups based on the condition of their pedal arteries. A study analyzed wound healing results by assessing both groups' wound closure and limb preservation degree. The statistical assessment used mean age with standard deviation and p-values to identify research outcomes. Results: 200 participants whose mean age was calculated to be 68.5 ± 10.2 years. The research showed that 120 patients (60%) maintained open pedal arteries after surgery, but 80 (40%) showed poor pedal blood flow. The patients with patent pedal arteries showed full wound healing at a rate of 85%, while the patients without patent arteries healed only at 55% (p < 0.01). The patent group achieved better limb salvage outcomes with a 90% rate compared to 65% in the non-patent group (p < 0.01). Positive pedal circulation in patients leads to faster wound healing while decreasing intervention requirements and enhancing clinical outcomes, proving pedal circulation's essential function in wound healing. Conclusion: A functioning pedal circulation network after bypass surgery leads to superior results during wound healing for patients diagnosed with CLTI. Pedal artery patency is an essential element that must be considered during the planning phases and postoperative treatment of patients in nursing procedures. Improving pedal blood flow lowers the risk of wound complications while enhancing the success rate of limb preservation, thus promoting better life quality among PAD patients with severe disease.